Exploration of the role of business schools in the development of world-class research universities - Sitnicki, Maksym (Technology audit and production reserves, 2017)
The object of research is the activity of 25 leading business schools in the world, functioning in the structure of research universities and contributing to their comprehensive development. One of the most problematic places is the question of further studying and in-depth analysis of the role of business schools in shaping the competitive advantages of research universities in the global environment. In the course of the research, the rating indicators of QS Global MBA Rankings were used, which includes 232 world-class business schools. To analyze the best 25 business schools in the world, scientific methods were used: generalization, analysis, synthesis, graphical method, and a comparison method. It is determined that the spheres of influence of business schools on the development of research universities are focused on: obtaining a significant financial resource; updating of intellectual potential and maintenance of a high level of entrepreneurial activity of students. This is due to the fact that the ratio of higher education expenditures to research and development work in the EU and the world has tendencies of substantial underfunding. The differences in the TOP 25 business schools of research universities in the world are systematized, characterized by significantly different training costs and the timing of the full cycle of MBA programs. The main regularities, which consist in the revealed systemic character of the recruitment process in the business schools of research universities and the preparation of people with creative entrepreneurial thinking are identified. This has a number of features, in particular in: – differentiation of payment and offers of alternative sources; – application of the principle – training in the process of work; – focusing on the development of comprehensive competencies in leadership; – preparation for work in complex, unfavorable situations caused by instability, limited resources and time; – opportunities for additional training or practice in partner business schools in other countries or on other continents. Thanks to this, it is ensured that MBA students receive a key competence – an entrepreneurial type of thinking. Compared with similar known traditional models of development of research universities, this ensures the renewal of the scientific potential of research universities and provides opportunities for increasing competitiveness at the global level